Biofunctionalization of 3D-printed silicone implants with immunomodulatory hydrogels for controlling the innate immune response: An in vivo model of tracheal defect repair. (January 2021) - Barthes, J.; Lagarrigue, P.; Riabov, V.; Lutzweiler, G.; Kirsch, J.; Muller, C.; Courtial, E.-J.; Marquette, C.; Projetti, F.; Kzhyskowska, J.; Lavalle, P.; Vrana, N.E.; et al.
Abstract: The recent advances in 3D-printed silicone (PDMS: polydimethylsiloxane) implants present prospects for personalized implants with highly accurate anatomical conformity. However, a potential adverse effect, such as granuloma formation due to immune reactions, still exists. One potential way to overcome this problem is to control the implant/host interface using immunomodulatory coatings. In this study, a new cytokine cocktail composed of interleukin-10 and prostaglandin-E2 was designed to decrease adverse immune reactions and promote tissue integration by fixing macrophages into M2 pro-healing phenotype for an extended period of time. In vitro, the cytokine cocktail maintained low levels of pro-inflammatory cytokine (TNF-α and IL-6) secretions and induced the secretion of IL-10 and the upregulation of multifunctional scavenging and sorting receptor stabilin-1, expressed by M2 macrophages. This cocktail was then loaded in a gelatine-based hydrogel to develop an immunomodulatory material that could be used as a coating for medical devices. The efficacy of this coating was demonstrated in an in vivo rat model during the reconstruction of a tracheal defect by 3D-printed silicone implants. The coating was stable on the silicone implants for over 2 weeks, and the controlled release of the cocktail components was achieved for at least 14 days. In vivo, only 33% of the animals with bare silicone implants survived, whereas 100% of the animals survived with the implant equipped with the immunomodulatory hydrogel. The presence of the hydrogel and the cytokine cocktail diminished the thickness of the inflammatory tissue, the intensity of both acute and chronic inflammation, the overall fibroblastic reaction, the presence of oedema and the formation of fibrinoid (assessed by histology) and led to a 100% survival rate. At the systemic level, the presence of immunomodulatory hydrogels significantly decreased pro-inflammatory cytokines such as TNF-α, IFN-γ, CXCL1 and MCP-1 levels at day 7 and significantly decreased IL-1α, IL-1β, CXCL1 and MCP-1 levels at day 21. The ability of this new immunomodulatory hydrogel to control the level of inflammation once applied to a 3D-printed silicone implant has been demonstrated. Such thin coatings can be applied to any implants or scaffolds used in tissue engineering to diminish the initial immune response, improve the integration and functionality of these materials and decrease potential complications related to their presence. Graphical abstract: Image 1